Time series forecasting of volatility using high frequency data - Tan, Hai Kang (2008)
This study attempts to investigate whether squared intra daily returns can be used to give superior estimates of volatility. In the existing literature, volatility models for daily returns are improved by including intraday information such as the daily high and low, volume, the number of trades, and intraday returns.